Fluoride-free synthesis of high-silica CHA-type aluminosilicates by seed-assisted aging treatment for starting gel. Issue 82 (28th September 2022) - Osuga, Ryota; Yabushita, Mizuho; Matsumoto, Takeshi; Sawada, Masato; Yokoi, Toshiyuki; Kanie, Kiyoshi; Muramatsu, Atsushi
Abstract : High-silica CHA -type aluminosilicates (Si/Al > 100) were successfully synthesized by seed-assisted aging treatment for starting gel without fluoride media. Abstract : High-silica CHA -type aluminosilicates (Si/Al molar ratio >100) were synthesized hydrothermally in the absence of fluoride media, where the seed-assisted aging treatment played an important role on the crystallization. These aluminosilicates showed a long catalytic lifetime with high selectivity toward lower olefins in the methanol-to-olefins reaction.